Functional Dyspepsia, Peptic Ulcer, and Helicobacter pylori Infection in a Rural Community of South Asia: An Endoscopy-Assisted Household Survey. Issue 4 (16th April 2021) - Rahman, M. Masudur; Ghoshal, Uday C.; Kibria, Md. Golam; Sultana, Nigar; Yusuf, M. Abdllah; Nahar, Shamsun; Ahmed, Faruque; Rowshon, AHM; Hasan, Mahmud
Abstract : INTRODUCTION: Functional dyspepsia (FD), although commoner than organic dyspepsia (OD) in-hospital studies, community data, particularly from rural areas, are lacking. We performed a rural community study in Bangladesh with the primary aims to evaluate (i) the prevalence of uninvestigated dyspepsia (UD), FD, and OD and (ii) the risk factors for UD. METHODS: This house-to-house survey was performed using a translated-validated enhanced Asian Rome III questionnaire and endoscopy with Helicobacter pylori tests, including genotyping. RESULTS: Of 3, 351/3, 559 responders ([94.15%], age 40.41 ± 16.05 years, female 1924 [57.4%]), 547 (16.3%) had UD (female 346 [18%] vs male 201 [14%]; P = 0.002); 201 (6%), 88 (2.6%), and 258 (7.7%) had postprandial distress (PDS), epigastric pain syndromes (EPS) and PDS-EPS overlap, respectively. On multivariate analysis, age >50 years (adjusted odds ratio [AOR] 1.34 [1.07–1.68]), female sex (AOR 1.42 [1.17–1.74]), being married (AOR 1.57 [1.21–2.07]), lower family income (AOR 1.79 [1.43–2.26]), nonsteroidal anti-inflammatory drug use (AOR 7.05 [2.11–23.55]), previous acute gastroenteritis (AOR 5.42 [1.83–16]), and psychological distress (AOR 5.02 [2.87–8.76]) were risk factors for UD. Of 346/547 (63.25%) undergoing endoscopy, 232 (67.05%) and 114 (32.95%) had FD and OD (peptic ulcers [PU] 99 [28.61%] and erosive esophagitis 13 [3.76%]). About 53% of FD subjects had EPS-PDS overlap, 32% had PDS, and only 15% had EPS. H. pylori was detected in 266/342 (78%) dyspeptics (FD 173/230 [75.2%], vs OD 92/114 [82.1%], P = 0.169). DISCUSSION: Sixteen percent, 11% and 5% of rural Bangladeshi Asian adults had UD, FD, and PU, respectively. One-third of UD subjects had OD, mostly PU.